Application of different doses of nitrogen fertilizer to improve the growth and yield of pakchong grass in post-tin mining land - Lestari, Tri; Rahmatika, Nurhuda; Pratama, Deni; Sitorus, Rostiar (Journal of Degraded and Mining Lands Management, 2025)
Post-tin mining land has low nutrient content, which makes it harder for plants to absorb macro and micronutrients. Adaptive plants such as pakchong grass and the application of nitrogen fertilizer are solutions for cultivating and increasing post-tin mining land productivity. This research was conducted to identify the most efficient doses of nitrogen fertilization for pakchong grass in post-tin mining land. This research was conducted in Kampoeng Reklamasi Air Jangkang, Bangka Regency. This research used a randomized block design consisting of 4 treatments, i.e., A0 (without N fertilizer), A1 (6.125 g N/plant), A2 (7.875 g N/plant), and A3 (9.875 g N/plant). Data obtained were subjected to analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test at a 95% significance level. The results showed that the application of different doses of nitrogen fertilizer significantly affected the dry weight of the canopy and yield per plot. The treatment of A3 (9.875 g N/plant) had the highest yield but was not significantly different from the A1 treatment (6.125 g N/plant) and A2 treatment (7.875 g N/plant). The highest fat content was in the A2 treatment (7.875 g N/plant), and the highest total N and protein content was in the A treatment (6.125 g N/plant). The best nitrogen treatment in this research was A1 (6.125 g N/plant), which had lower nitrogen treatment but had similar results with the higher dose of other nitrogen fertilizer, making it more efficient for nitrogen fertilization in post-tin mining land.